Customer-Based Brand Equity, Company Reputation and Product Quality Effect on Customer Loyalty: Air Conditioner Retail Market in Medan - Suwarno, Bambang; Prassetyawan, Anjas; Abbas, Muhammad (Publisher Cv. Inara, 2023)
This research explores and focuses on customer perceptions, because there is still a lack of research in knowing the relationship between customer perceptions of products and retail stores. Data collection by interviews, questionnaires, and observations on Panasonic AC retail customers. This study tries to examine the influence of the dimensions of customer loyalty which are influenced by the dimensions of Customer Based Brand Equity (CBBE), Company Reputation and Product Quality. This research is associative, with a quantitative method approach. The research was validated using SPSS-26 with data analysis techniques using multiple linear regression analysis. The results showed that CBBE and product quality had a positive and significant effect on customer loyalty. Furthermore, the company's reputation partially has a positive but not significant effect on customer loyalty. Whereas CBBE, Company Reputation, and Product Quality simultaneously have a positive and significant effect on Customer Loyalty. From the results of this study, it was also concluded that there is a tendency for loyal customers to not guarantee that they will recommend the products they buy to others. Product (brand) selection recommendations are also more influenced by salespeople in retail stores where customers will buy products. From this research, it was found that the novelty of customer perceptions of company reputation has no effect on customer loyalty, especially for retail store customers.